2021
DOI: 10.1038/s41590-021-00927-z
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of T cell aging

Abstract: ge erodes every physiological function and affects most, if not all, cell types of our body through a series of mechanisms that range from the loss of genomic stability and epigenetic alterations to the loss of proteostasis, deficient nutrient signaling, mitochondrial dysfunction, cellular senescence, stem cell exhaustion, and deviant intercellular communication. Most of these 'hallmarks of aging' 1 have been defined in non-vertebrate animal models (such as nematodes and flies) that lack sophisticated adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
274
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(282 citation statements)
references
References 154 publications
(192 reference statements)
8
274
0
Order By: Relevance
“…Aging is also associated with crucial changes in the adaptive immune response. Aged T cells displayed reduced proliferative capacity and an increased production of pro-inflammatory cytokines (8,9), thereby contributing to a chronic state of low-grade inflammation, called 'inflammaging'. The age-related defects in CD4 + T cell helper function also impaired B cell responses (10).…”
Section: Introductionmentioning
confidence: 99%
“…Aging is also associated with crucial changes in the adaptive immune response. Aged T cells displayed reduced proliferative capacity and an increased production of pro-inflammatory cytokines (8,9), thereby contributing to a chronic state of low-grade inflammation, called 'inflammaging'. The age-related defects in CD4 + T cell helper function also impaired B cell responses (10).…”
Section: Introductionmentioning
confidence: 99%
“…In opposition, others demonstrated that human CD57-positive and CD57-negative T cells exhibit similar proliferation properties [105]. Altogether, it appears that T cells undergo cellular aging and senescence and that their functions are intrinsically or extrinsically diminished [94]. Keeping in mind that human T cells collected from a 60-year-old donor already displayed high levels of senescence markers, it is easy to speculate that the efficacy of ICI is likely already diminished at that age [59].…”
Section: Are T Cells Really Senescent?mentioning
confidence: 99%
“…A big question in the field is whether T cells truly become senescent during aging and if it affects their functions [ 94 ]. The first evidence came when the expression of the senescence marker p16 was found increased in circulating T cells collected from both aged mice and humans [ 95 , 96 ].…”
Section: Age-associated Mechanisms Affecting the Efficacy Of Immunotherapymentioning
confidence: 99%
“…While very effective in keeping cancer at bay during our reproductive years, the immune system itself undergoes a progressive decline with aging, contributing to the establishment of the so-called "immunosenescence" [35,36]. For instance, aging is characterized by a decline in macrophage metabolic and immune function, with a reduced clearance and immunosurveillance capacity [37].…”
Section: Immune Surveillancementioning
confidence: 99%
“…T cell response undergoes major age-dependent changes that gradually compromise its main functionality. Thymic involution, mitochondrial dysfunction, genetic and epigenetic alterations, loss of proteostasis, and eventually senescence have all been reported to affect T lymphocyte function, and consequently, the proper activation of a complete adaptive response [35].…”
Section: Immune Surveillancementioning
confidence: 99%